Sequential Integration of Microenvironment Regulation Utilizing Aggregation‐Induced Emission Luminogen‐Based Carbon Dots for Diabetic Wound Treatment - Judun Zheng; Miaomiao Kang; Minghai Zhao; Shuang Guo; Qihu Xie; Zhijin Fan; Sitong Zhou; Zhijun Zhang; Qin Zeng; Zeyu Liu; Yinghui Liu; Jialin Huang; et al. (Small, 2026)
ABSTRACT Effective management of diabetic wound healing remains challenging due to the complex wound microenvironment, characterized by persistent infections and inflammation, as well as obstacles in tissue repair, including impaired extracellular matrix (ECM) remodeling and re‐epithelialization. Herein, we propose a sequential integrating microenvironment regulation and re‐epithelialization promotion (SIMREP) strategy based on zinc‐doped glycyrrhizinate carbon dots loaded with aggregation‐induced emission luminogens (AIEgens), namely TTPy‐Zn@GCDs for accelerated diabetic wound healing. TTPy‐Zn@GCDs effectively inhibit bacterial infection through AIEgen‐based photodynamic therapy and promote the M2‐phenotype polarization of macrophages by eliminating reactive oxygen species. Remarkably, TTPy‐Zn@GCDs not only present a superior ECM remodeling ability by suppressing the overexpression of matrix metalloproteinase (MMP)‐9 in diabetic wounds, but also promote keratinocyte migration and accelerate the re‐epithelialization process by activating the hypoxia‐inducible factor‐1α (HIF‐1α) signaling pathway. Together, the SIMREP strategy offers a promising approach for accelerating the healing process of infected diabetic wounds.